Arabinoxylan-Based Mucoadhesive Oral Films of Tizanidine HCL Designed and Optimized Using Central Composite Rotatable Design. Issue 5 (24th March 2018) - Zaman, Muhammad; Hanif, Muhammad; Khan, Mahtab Ahmad
ABSTRACT: In the current study, a natural pharmaceutical excipient, arabinoxylan, was extracted from ispaghula husk and used to develop controlled release of mucoadhesive oral films of tizanidine hydrochloride. Film formulations were designed and optimized by central composite rotatable design, selecting arabinoxylan ( X 1 ) and glycerol ( X 2 ) as variables. Prepared films were evaluated for chemical compatibility of the ingredients, surface morphology, mechanical strength, in vitro drug release, ex vivo drug permeation and ex vivo mucoadhesion strength. Results revealed that selected ingredients were compatible and quite capable of producing films with desired characteristics. GRAPHICAL ABSTRACT: